PlantGF: an analysis and annotation platform for plant gene families. (2nd February 2022) - Li, Jiaxuan; Yang, Shuai; Yang, Xiaojie; Wu, Hui; Tang, Heng; Yang, Long
Abstract: Gene families contain genes that come from the same ancestor and have similar sequences and structures. They perform certain specific functions within and among different species. Currently, there is no complete process or platform for the rapid analysis of plant gene families. In this study, a comprehensive query and analysis platform of plant gene families, the Plant Gene Family Platform (PlantGF), was constructed. The platform is composed of four main parts: Search, Tools, Statistics and Auxiliary. A total of 2 909 580 gene family members were identified from 138 plant species in PlantGF. The data can be queried in the Search section through a user-friendly interface. A general process for gene family analysis, having nine steps, is provided. The platform also includes four online tools (HMM-Search, BLAST, MAFFT and HMMER) in the Tools section for useful additional analyses. The statistical analysis of the relevant gene families is shown on the Statistics page. Auxiliary pages are provided for data downloading. The datasets for all 138 plant species' protein sequences and their gene families can be acquired on the Download page. A user's manual and some useful links are displayed on the Manual and Links pages, respectively. To the best of our knowledge, PlantGF is the first comprehensive platform for studying plant gene families, and it will make important contributions to plant gene family-related research. Database URL : http://biodb.sdau.edu.cn/PGF/index.html